Synthesis and Biological Evaluation of Dantrolene‐Like Hydrazide and Hydrazone Analogues as Multitarget Agents for Neurodegenerative Diseases. (22nd June 2021) - Bolognino, Isabella; Giangregorio, Nicola; Tonazzi, Annamaria; Martínez, Antón L.; Altomare, Cosimo D.; Loza, María I.; Sablone, Sara; Cellamare, Saverio; Catto, Marco
Abstract: Dantrolene, a drug used for the management of malignant hyperthermia, had been recently evaluated for prospective repurposing as multitarget agent for neurodegenerative syndromes, including Alzheimer's disease (AD). Herein, twenty‐one dantrolene‐like hydrazide and hydrazone analogues were synthesized with the aim of exploring structure‐activity relationships (SARs) for the inhibition of human monoamine oxidases (MAOs) and acetylcholinesterase (AChE), two well‐established target enzymes for anti‐AD drugs. With few exceptions, the newly synthesized compounds exhibited selectivity toward MAO B over either MAO A or AChE, with the secondary aldimine 9 and phenylhydrazone 20 attaining IC50 values of 0.68 and 0.81 μM, respectively. While no general SAR trend was observed with lipophilicity descriptors, a molecular simplification strategy allowed the main pharmacophore features to be identified, which are responsible for the inhibitory activity toward MAO B. Finally, further in vitro investigations revealed cell protection from oxidative insult and activation of carnitine/acylcarnitine carrier as concomitant biological activities responsible for neuroprotection by hits 9 and 20 and other promising compounds in the examined series. Abstract : Simpler is better : Structural modifications of the chemical structure of dantrolene, previously disclosed as a repositionable drug with potential for Alzheimer's disease, allowed preparing new small molecules with multitarget activity profile. Compared to dantrolene, molecular simplification resulted in less toxic and more soluble compounds. Some of them had higher potency as selective MAO B inhibitors, and were effective in cell protection from oxidative insult and in the activation of CAC carnitine carrier.